Brassinosteroids Positively Regulate Plant Immunity via BRI1-EMS-SUPPRESSOR 1-Mediated GLUCAN SYNTHASE-LIKE 8 Transcription - Xiong, Jiawei; Wan, Xiaoping; Ran, Maolin; Xu, Xiumei; Chen, Lezhang; Yang, Feng (Frontiers in Plant Science, 2022)
Plant hormone brassinosteroids (BRs) play key roles in plant adaptation to biotic stresses, including various pathogen infections. As a core factor in BR signaling, the transcription factor BRI1-EMS-SUPPRESSOR 1 (BES1) activates BR responses via regulating the expression of target genes. However, the molecular mechanism of BRs in regulating plant immunity is unclear, and the key components are not identified. In this study, we found that BR biosynthesis and signaling transduction are essential for plant resistance to pathogen infection, and BR biosynthesis or BR signaling-deficient mutants displayed susceptibility to Pseudomonas syringae pv. tomato DC3000 (Pst DC3000) infection [including more serious symptoms and more photosystem II (PSII) photochemistry damage]. We identified a callose synthase gene GLUCAN SYNTHASE-LIKE 8 (GSL8) as a direct target of BES1, and its expression was induced by BRs/BES1. Meanwhile, BRs induced callose accumulation after Pst DC3000 infection. Moreover, BES1 gain-of-function mutant bes1-D showed promoted Pst DC3000 resistance. GSL8 T-DNA insertion mutant gsl8-1 was susceptible to DC3000, while brassinolide (BL) treatment partially rescued gsl8-1 susceptible phenotypes. Our study suggests that BR-induced pathogen resistance partly depends on the BR-induced BES1-GSL8 cascade to mediate callose accumulation.